Autofocusing method for lensless digital in-line holographic microscopy with misaligned illumination - Dudek, Julia; Rogalski, Mikołaj; Winnik, Julianna; Arcab, Piotr; Zdańkowski, Piotr; Trusiak, Maciej (Photonics Letters of Poland, 2024)
This study presents a correction method in Lensless Digital In-line Holographic Microscopy accounting for tilted illumination to address challenges caused by misalignments in the optical setup. An autofocusing method is discussed, utilizing a sharpness criterion based on amplitude variance to find both propagation distance and illumination tilt for precise holographic reconstruction of phase objects. The proposed algorithm was rigorously tested under large illumination angles, demonstrating its effectiveness in maintaining high reconstruction quality for demanding imaging scenarios. Full Text: PDF References Z. Huang and L. Cao, "Deep learning sheds new light on non-orthogonal optical multiplexing", Light Sci Appl 13, 145 (2024). CrossRef V. Balasubramani, M. Kujawińska, C. Allier, V. Anand, C.-J. Cheng, C. Depeursinge, N. Hai, S. Juodkazis, J. Kalkman, A. Kuś, M. Lee, P.J. Magistretti, P. Marquet, S.H. Ng, J. Rosen, Y.K. Park, and M. Ziemczonok, "Roadmap on Digital Holography-Based Quantitative Phase Imaging", J. Imaging 7, 252 (2021). CrossRef V. Anand, T. Katkus, D.P. Linklater, E.P. Ivanova, S. Juodkazis, "Lensless Three-Dimensional Quantitative Phase Imaging Using Phase Retrieval Algorithm", J. Imaging 6, 99 (2020). CrossRef A. Ozcan, E. McLeod, "Lensless Imaging and Sensing", Annual Review of Biomedical Engineering 18, 77 (2016). CrossRef C.J. Potter, Z. Xiong, E. McLeod, "Clinical and Biomedical Applications of Lensless Holographic Microscopy", Laser Phot. Rev. 18, 2400197 (2024). CrossRef N.N. Evtikhiev, S.N. Starikov, P.A. Cheryomkhin, V.V. Krasnov, V.G. Rodin, "Numerical and optical reconstruction of digital off-axis Fresnel holograms", Proc. SPIE 8429, 84291M (2012). CrossRef T. Wu, Y. Yang, H. Wang, H. Chen, H. Zhu, J. Yu, X. Wang, "Investigation of an Improved Angular Spectrum Method Based on Holography", Photonics 11, 16 (2024). CrossRef M. Trusiak, J.-A. Picazo-Bueno, P. Zdankowski, V. Micó, "DarkFocus: numerical autofocusing in digital in-line holographic microscopy using variance of computational dark-field gradient", Optics and Lasers in Engineering 134, 106195 (2020). CrossRef F. Dubois, C. Schockaert, N. Callens, C. Yourassowsky, "Focus plane detection criteria in digital holography microscopy by amplitude analysis", Opt. Express 14, 5895 (2006). CrossRef Y. Zhang, H. Wang, Y. Wu, M. Tamamitsu, A. Ozcan, "Edge sparsity criterion for robust holographic autofocusing", Opt. Lett. 42, 3824 (2017). CrossRef Z. Ren, Z. Xu, E.Y. Lam, "Learning-based nonparametric autofocusing for digital holography", Optica 5, 337 (2018). CrossRef R.W. Gerchberg, W.O. Saxton, "A Practical Algorithm for the Determination of Phase from Image and Diffraction Plane Pictures", Optik 35, 237 (1972). CrossRef J.R. Fienup, "Phase retrieval algorithms: a comparison", Appl. Opt. 21, 2758 (1982). CrossRef T.-C. Poon, T. Kim, G. Indebetouw, B.W. Schilling, M.H. Wu, K. Shinoda, Y. Suzuki, "Twin-image elimination experiments for three-dimensional images in optical scanning holography", Opt. Lett. 25, 215 (2000). CrossRef Y. Rivenson, Y. Wu, H. Wang, Y. Zhang, A. Feizi, A. Ozcan, "Sparsity-based multi-height phase recovery in holographic microscopy", Sci. Rep. 6, 37862 (2016). CrossRef M. Rogalski, P. Arcab, L. Stanaszek, V. Micó, C. Zuo, M. Trusiak, "Physics-driven universal twin-image removal network for digital in-line holographic microscopy", Opt. Express 32, 742 (2024). CrossRef Y. Rivenson, Y. Wu, A. Ozcan, "Deep learning in holography and coherent imaging", Light Sci. Appl. 8, 85 (2019). CrossRef